A study of X2 and S1 Handover in LTE Networks using MATLAB - Singh, B; Yadav, M (International Journal of Computer Sciences and Engineering, 2025)
A load balancing method is proposed for the long term evolution networks. Today the traffic on networks is growing because of huge requirement of higher data rates for e.g. for Video streaming, Video conferencing, Online gaming etc. This demand results in excess load on the networks due to which the networks suffer from the heavy load and the quality of networks get degraded. The Load balancing is achieved between the loaded cell and its neighbor cells which are directly connected to each other and one of them have enough available resources so that the load can be shared with the neighbor node. In this work, we have proposed a method for load balancing in LTE networks which shows the simulation of two scenarios in which the handover is done between the LTE to LTE and LTE to Non LTE network nodes done